CHILD'S BILE TRACT ATHERIA: DIAGNOSIS AND TREATMENT PROBLEMS. - Suvonkulov Uktam Toirovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Biliary tract atresia (BAT) in children is a rare but serious disease that leads to impaired bile outflow from the liver and often causes chronic liver failure. The article examines modern approaches to the diagnosis and treatment of ARF, including the use of  ultrasound  and  cholangiography  to  confirm  the  diagnosis,  as  well  as  surgical intervention (Kasaya's surgery) as the primary treatment method. Long-term treatment outcomes and the prospects of new methods, such as gene therapy and the use of stem cells,  are  also  analyzed.  Data  from  Google  Scientific,  Scopus,  and  other  scientific databases were used to present current information on biliary tract diseases. The article emphasizes  the  need  for  early  diagnosis  and  timely  intervention  to  improve  the prognosis and quality of life of children with ASD.